Synthesis of Mevalonate Pathway Lipids in Fibroblasts from Zellweger and X-linked ALD Patients - Appelkvist, Eeva-Liisa; Venizelos, Nikolaos; Zhang, Yiyi; Parmryd, Ingela; Hagenfeldt, Lars; Dallner, Gustav (Pediatric research, 1999)
Fibroblasts were cultured to determine the involvement of peroxisomes in cholesterol and dolichol synthesis. For this purpose, the behavior of cells from patients with Zellweger syndrome, with X-linked adrenoleukodystrophy, and from nondiseased control subjects was studied. Cells both after pretreatment with mevinolin and without pretreatment were incubated in a medium containing [3H]-mevalonate. In fibroblasts from patients with peroxisomal defects, the cholesterol content and mevalonate incorporation into cholesterol were decreased by 10-20% in comparison with control cells. Mevinolin pretreatment decreased the incorporation rate of [3H]-mevalonate into cholesterol but increased the labeling of ubiquinone and dolichol both in diseased and control cells. Squalene synthase activity was unchanged, whereas the activity of farnesyl-pyrophosphate synthase was increased in the diseased states. The results show that in patients with peroxisomal deficiency neither the amount nor the rate of synthesis of cholesterol and dolichol is reduced to any greater extent.